PROSTATE CANCER METASTASIS TO CERVICAL NODE CHAIN-AN UNUSUAL CLINIC-PATHOLOGICAL FINDING - Iftikhar, Haissan; Ikram, Mubasher; Usman, Mohammad; Ghaloo, Shayan Khalid (Journal of Ayub Medical College Abbottabad, 2018)
Prostate carcinoma is one of the most common cancers in males all around the world. Head and neck squamous cell carcinoma is amongst the leading carcinoma in men specially in the sub-continent. There are around 150 lymph nodes on either side in the neck and cervical lymph nodes are a common site for head and neck malignancies to metastasize however carcinoma of prostate may in rare cases metastasize to cervical chain, therefore warranting a neck dissection. In case of unknown primary of head and neck extensive work up is required to find the primary site. Our case provided a similar picture with a single enlarged node which on biopsy to our surprise revealed adenocarcinoma of prostate. Keywords: Neoplasm; prostate, neck; lymph node; Metastasis